1996
DOI: 10.1172/jci118400
|View full text |Cite
|
Sign up to set email alerts
|

Human diabetes associated with defects in nuclear regulatory proteins for the insulin receptor gene.

Abstract: The control of gene transcription is mediated by sequencespecific DNA-binding proteins ( trans -acting factors) that bind to upstream regulatory elements ( cis elements). We have previously identified two DNA-binding proteins that specifically interact with two unique AT-rich sequences of the 5 Ј regulatory region of the insulin receptor gene which have in vivo promoter activity. Herein we have investigated the expression of these DNA-binding proteins in cells from two unrelated patients with insulin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…The above observations were supported further by the evaluation of transcriptional regulation of the IR gene in EBV-transformed lymphoblasts from one patient with the usual features of type 2 diabetes, in which defects in nuclear proteins regulating the IR gene were previously reported (2). In EBV-transformed lymphoblasts from this patient, IR expression was decreased despite the fact that the IR gene was normal (2). As shown in Fig.…”
Section: Vol 23 2003 Regulation Of the Insulin Receptor Gene Promotsupporting
confidence: 81%
“…The above observations were supported further by the evaluation of transcriptional regulation of the IR gene in EBV-transformed lymphoblasts from one patient with the usual features of type 2 diabetes, in which defects in nuclear proteins regulating the IR gene were previously reported (2). In EBV-transformed lymphoblasts from this patient, IR expression was decreased despite the fact that the IR gene was normal (2). As shown in Fig.…”
Section: Vol 23 2003 Regulation Of the Insulin Receptor Gene Promotsupporting
confidence: 81%
“…Previous studies have reported similar findings concerning the effect of insulin on the expression of transcription factors (Hansen et al 2004;Rome et al 2003). Overall, these above transcription factors signaling pathways are essential for the energy metabolism and intracellular signaling pathways to adapt to environmental changes, such as insulin, and may also participate in the pathogenesis of the disease (Barroso et al 1999;Brunetti et al 1996).…”
Section: Gadd45bsupporting
confidence: 59%
“…This attractive hypothesis is supported by the recent identification of mutated transcription factors in subtypes of maturity-onset diabetes of the young (39,40) and in other particular forms of type 2 diabetes (13,14). If this also occurs in the common form of type 2 diabetes, one can predict that the impaired regulation of gene expression may play a primary role in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that environmental factors play a major role in type 2 diabetes, in addition to genetic predisposition. Alterations in the transcriptional mechanisms involved in the adaptation of the cells to environmental changes may thus participate in the pathogenesis of the disease (13,14). In keeping with this hypothesis, the expression of some important genes involved in insulin action and glucose metabolism has been found to be altered in peripheral tissues of type 2 diabetic patients.…”
mentioning
confidence: 78%